The social support, psychological resilience and quality of life of nurses in infectious disease departments in China: A mediated model. (9th November 2022) - Yan, Jiaran; Wu, Chao; He, Chunyan; Lin, Yawei; He, Shizhe; Du, Yanling; Cao, Baohua; Lang, Hongjuan
Abstract: Aim: This paper aimed to investigate the relationship between social support and quality of life for nurses in infectious disease departments in China, as well as the function of psychological resilience in mediating this relationship. Background: Nurses in infectious disease departments play a critical role in the prevention and control of infectious diseases and in public health care services in general, and their quality of life can affect the quality of clinical nursing work they do. However, there are few studies on the relationship between nurses' social support networks and their quality of life. Methods: A cross‐sectional study was conducted using a sample of 866 clinical nurses from the infectious disease departments of 10 general hospitals in China. Data were collected using a questionnaire survey from January to May 2021. The mediating influence of psychological resilience on social support and quality of life was investigated using structural equation modelling. Results: The score of quality of life was (36.36 ± 7.64). Quality of life was positively correlated with social support and psychological resilience ( r 1  = 0.521, r 2  = 0.583; p  < .01), and psychological resilience was positively correlated with social support ( r  = 0.426; p  < .01) as well. The mediating effect of psychological resilience between social support and quality of life was 0.233, accounting for 37% of the total effect. Conclusion: The quality of life of nurses working in infectious disease departments is in the middle level. Psychological resilience is a mediating variable between social support and quality of life. Implications for Nursing Management: Managers can improve the quality of life of nurses by both increasing social support and strengthening psychological resilience. Managers should pay attention to the degree of social support provided to nurses and take proactive measures to build psychological resilience so that nurses can effectively manage stress and negative emotions from work and life in order improve their quality of life.